2006
DOI: 10.5194/angeo-24-1429-2006
|View full text |Cite
|
Sign up to set email alerts
|

Equatorial scintillations in relation to the development of ionization anomaly

Abstract: Abstract. The irregularities in the electron density distribution of the ionosphere over the equatorial region frequently disrupt space-based communication and navigation links by causing severe amplitude and phase scintillations of signals. Development of a specification and forecast system for scintillations is needed in view of the increased reliance on spacebased communication and navigation systems, which are vulnerable to ionospheric scintillations. It has been suggested

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 13 publications
1
35
0
Order By: Relevance
“…Similarly from Fig. 2b There are several studies relating the equatorward TEC gradient with the occurrence of post-sunset scintillations (Raghavarao et al, 1988;Ray et al, 2006). This is perhaps for the first time that efforts are being made to correlate occurrence of post-sunset scintillations with the poleward TEC gradient in the Indian longitude sector.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly from Fig. 2b There are several studies relating the equatorward TEC gradient with the occurrence of post-sunset scintillations (Raghavarao et al, 1988;Ray et al, 2006). This is perhaps for the first time that efforts are being made to correlate occurrence of post-sunset scintillations with the poleward TEC gradient in the Indian longitude sector.…”
Section: Resultsmentioning
confidence: 99%
“…Several workers have studied the plausible causes and effects (Ray et al, 2006; , 2001, 2004Rama Rao et al, 2006;Ram et al, 2006;Nava et al, 2007) of such steep TEC gradients and have strived to develop a predictive mechanism for occurrence for post-sunset scintillations. These exercises have mostly been restricted to the region between the magnetic equator and the northern and southern crests of EIA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, during September the results show that the differences of the mean peak drift velocities are very marginal and not so significant between the three cases analyzed here, which suggests that other agents could be operating for the plasma instability to occur. Anderson et al (2004) investigated the night-to-night occurrence of post-sunset equatorial scintillation activity in the Peruvian/Chilean longitude sectors (years 1998-1999), and reported that a threshold velocity of 20 ms -1 for the E 9 B drift will determine whether the UHF scintillation index S 4 will be greater than 0.5 after 20:00 LT. Ray et al (2006) examined in the Indian sector the relationship between the maximum F-layer base height velocity and the post-sunset L-band scintillation, and found that the E 9 B drift velocity (dh 0 F/dt) is more reliable (80%) in forecast lower scintillation levels (S 4 \ 0.4) then their higher scintillations (43% for S 4 [ 0.4). Again, from Indian sector, Dabas et al (2007) showed that for the 4 GHz scintillation to be observed at a low latitude station the threshold in the E 9 B drift velocity should be approximately twice (*30 ms -1 ) the peak velocity in the situation of scintillation only near the magnetic equator.…”
Section: E 9 B Vertical Drift Velocity Electron Density Gradient Andmentioning
confidence: 98%
“…As in the post-sunset hours the large electric field PRE causes the resurgence of the equatorial fountain effect, the ionosphere at latitudes surrounding the geomagnetic equator and adjacent to the enhanced anomaly crests tends to exhibit remarkable spatial gradients of the electron distribution (Ray et al 2006). Thus, a well-developed large scale bubble that expands/extends along the magnetic field lines may intersect those regions of increased background electron density and sharp ionospheric gradients and, consequently, set up at the walls of the bubbles a secondary instability processes that will create conditions favorable for the generation of smaller scale plasma irregularities (Muella et al 2010).…”
Section: E 9 B Vertical Drift Velocity Electron Density Gradient Andmentioning
confidence: 98%